PUTUSAN PEMIDANAAN TERHADAP ANGGOTA MILITER YANG MELAKUKAN TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENYEBABKAN ORANG LAIN MENINGGAL DUNIA - Ndruru, Damai Selamat (LPPM Universitas Nias Raya, 2025)
An event that results in damage when a motor vehicle collides with another item is called a traffic accident. These mishaps can occasionally cause harm or even death to people or animals. A panel of judges at the Military Court I-05 Pontianak is trying one of the criminal actions related to a traffic accident that results in the death of another person; this case is represented by Decision Number 23-K/PM I-05/AD/IV/2017. In this ruling, the judge found that the defendant had been legally and persuasively shown guilty of operating a motor vehicle negligently, which caused a collision that claimed another person's life. The defendant was given a seven-month jail sentence. The study judgment number 23-K/PM I-05/AD/IV/2017 is titled